Arranjos organizacionais no sistema agroindustrial do leite : uma proposta a partir da análise de redes no Estado do Paraná - Ferreira, Maria Clara Melo (2014)
The Dairy Agribusiness System in Brazil has a major important role in the economic, social scenario having reached its peak development in the nineties driven by changes in the economy as well as in the institutional and organizational environments of the country. However, for a part of rural producers, especially those involved in lowscale production, the new scenario brought several challenges where the maintenance of productive activity became imperative. It can be reached through several strategies, such as, the formation of collective structures or organizational arrangements more adequated to the new economic, institutional and organizational environment. In this context, the objective of this study was to verify whether the formation of collective actions in rural production is able to benefit the relationship with other agents or institutions of the dairy agribusiness system. To this purpose, we developed semistructured questionnaires submitted to 120 rural dairy producers between August 2012 and February 2013 in three regions of the Parana state. The networks found in the three studied regions were characterized as asymmetric social networks with relationships between agents built upon mutual reliability. There are no written contracts to formalize the transactions but there is a mutual adjustment between the parts. An individual analysis of the networks revealed that the region of Santa Izabel do Oeste presented an organized and structured network of cooperation with cultural and social questions that facilitated the formation of collective action enabling higher flow of information, which generated higher competitive advantages for the rural producers of the region compared with the remaining regions. A network characterized by weak bonds between agents in Marechal Candido Rondon provokes gaps in the network, although not interfering negatively in the flow of information. The producers from this region had an intermediate competitive advantage when compared with the other two regions. Among the evaluated regions, Maringa is the one with the lowest level of organization and allowed the lowest competitive advantage for its agents. This study indicated that among the evaluated rural producers those involved in collective actions established more satisfactory relationships with the remaining agents of the productive chain developing more competitiveness towards producers working individually.